Evaluation of the Diagnostic Role of Gata3 Immunohistochemistry on Cytology Specimens for Metastatic Breast Carcinoma - Eaman Suud Khalifa; Ayser Hameed Latif (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: Distinguishing of metastatic breast carcinoma from nonmammary metastatic carcinomas by cytological examination might have some difficulties. The sensitivity of traditional tumor markers for immunostaining might be not high enough . The role of GATA3 immunohistochemistry as a novel marker of primary and metastatic stages of breast carcinoma in specimens of fine needle aspiration was evaluated.Materials and Methods: Sections were taken from 73 cases of FNA samples of metastatic malignancies including 38 metastatic breast cancer and 35 nonmammary malignancies were stained with GATA3 immunohistochemical marker. Samples of FNA were taken from pleural effusion, ascetic fluid and lymph nodes. Results: Eighty-nine percent (34/38) of metastatic breast carcinoma cases were regarded as GATA3 positive expression , while all nonmammary adenocarcinoma samples were GATA3 negative . Most of GATA3 positive samples showed intense nuclear staining in the majurity of the malignant cells.Conclusions: GATA3 staining is an important addition to immunohistochemical panels for fine needle aspiration samples for distinguishing metastatic breast carcinoma from other malignancy.